Estimation of The Zenith Path Delay using RTK-DGPS measurements - Muhammed, Reyam R.; Mahdi, Alaa S. (Iraqi Journal of Science, 2018)
In this paper, the method of estimating the variation of Zenith Path Delay (ZPD) estimation method will be illustrate and evaluate using Real Time Kinematic Differential Global Positioning System (RTK-DGPS). The GPS provides a relative method to remotely sense atmospheric water vapor in any weather condition. The GPS signal delay in the atmosphere can be expressed as ZPD. In order to evaluate the results, four points had been chosen in the university of Baghdad campus to be rover ones, with a fixed Base point. For each rover position a 155 day of coordinates measurements was collected to overcome the results. Many models and mathematic calculations were used to extract the ZPD using the Matlab environment. The result shows that the ZPD values in mm depend on the water vapor intensity in the atmosphere and the mean temperatures. Also, the mean temperature model can be generated to calculate the Water Vapor Intensity( WVI( for 20 km highest.